2014
DOI: 10.4090/juee.2014.v8n1.003010
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Reynolds Number of Air Flow to the Particle Collection Efficiency of a Fibrous Filter Medium With Cylindrical Section

Abstract: Abstract:At this study an attempt for the theoretical approach of the Reynolds number effect of air flow to the particle collection efficiency of a fibrous filter with cylindrical section will be made. Initially, a report of the air filtration models to fibrous filter media will be presented along with an explanation of both the parameters and the physical quantities which govern the air filtration process. Furthermore, the resulting equation from the mathematical model will be applied to a real filter medium … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…s), we expected and confirmed that actual outflow rates are much lower. This is due to very high Reynolds number for high air flow rate indicating non-laminar flow and increases in Mach number at higher pressures due to compressible air [33][34][35] . Flow rate saturates for each tubing configuration at approximately 200 mmHg vacuum (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…s), we expected and confirmed that actual outflow rates are much lower. This is due to very high Reynolds number for high air flow rate indicating non-laminar flow and increases in Mach number at higher pressures due to compressible air [33][34][35] . Flow rate saturates for each tubing configuration at approximately 200 mmHg vacuum (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to very high Reynolds number for high air flow rate indicating non-laminar flow and increases in Mach number at higher pressures due to compressible air. 26,33,34 Flow rate saturates for each tubing configuration at approximately 200 mmHg vacuum (Figure 5A) indicating higher order compressibility and turbulent flow effects, which are not modeled by Hagen-Poiseuille, influence the response. In our experience, the mixed setup (2 HEPA filters, 1.8 m of ventilator tubing and 3.2 m of 7 mm diameter suction tubing) would provide good balance between outflow rate, filter efficiency and easy of setup.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamics of aerosol particles must be understood in order to apply a filtration model. It is worth noting that filters are primarily designed for laminar airflow which is indicated by a relatively low Reynolds number of less than 2000 [40].…”
Section: Data Availability Statementmentioning
confidence: 99%